Revision einiger Typen der von Otto Schmiedeknecht beschriebenen paläarktischen Ichneumonidae (Hymenoptera). - Horstmann, Klaus (Contributions to Entomology = Beiträge zur Entomologie, 1990)
The types of Western Palaearctic Ichneumonidae (Hymenoptera) described by Otto Schmiedeknecht are scattered over at least 21 museums. Some of these collections are characterized and the possible types existing in them are listed. Revisions of 91 species and varieties are compiled, including all taxa, the types of which are not found in Schmiedeknecht's personal collections in Berlin and Rudolstadt. Lectotypes are designated for 22 taxa, and 13 new synonyms are indicated. A new name Trematopygodes rarus, is given to Trematopygodes blancoburgensis of authors, not of Schmiedeknecht. Nine taxa could not be interpreted, their types being lost. In an appendix 98 species described by Förster and published by Schmiedeknecht are discussed. Nomenclatural Actsdebilis Schmiedeknecht, 1911 (Acroblapticus), Lectotype now a synonym of Gnathochorisis dentifer (Thomson, 1888)thomsoni Schmiedeknecht, 1911 (Adelognathus), Lectotypekrapinensis Schmiedeknecht, 1930 (Amblyteles hungaricus var.), syn. n. of Eutanyacra glaucatoria (Fabricius, 1793)alticola Schmiedeknecht, 1910 (Banchus volutatorius var.), Lectotype now a synonym of Banchus volutatorius (Linnaeus, 1758)gaullei Schmiedeknecht, 1896 (Cryptus), syn. n. of Synechocryptus levaillantii (Lucas, 1849)dimidiatipennis Schmiedeknecht, 1905 (Hemiteles), Lectotype now a synonym of Obisiphaga stenoptera (Marshall, 1868)disputabilis Schmiedeknecht, 1897 (Hemiteles), Lectotype; syn. n. of Mastrulus marshalli (Bridgman & Fitch, 1882)blancoburgensis Schmiedeknecht, 1928 (Ichneumon), Lectotype; syn. n. of Ichneumon cerinthius Gravenhorst, 1820faroensis Schmiedeknecht, 1938 (Ichneumon), syn. n. of Ichneumon ligatorius Thunberg, 1822henschi Schmiedeknecht, 1929 (Ichneumon), syn. n. of Barichneumon anator (Fabricius, 1793)scanicus Schmiedeknecht, 1929 (Ichneumon), syn. n. of Ichneumon corfitzi Thomson, 1890annulicornis Schmiedeknecht, 1928 (Ichneumon derasus var.), syn. n. of Virgichneumon monostagon (Gravenhorst, 1820)bipunctatus Schmiedeknecht, 1928 (Ichneumon derasus var.), syn. n. of Coelichneumon haemorrhoidalis (Gravenhorst, 1829)nigricornis Schmiedeknecht, 1928 (Ichneumon rubricosus var.), syn. n. of Gareila tenebrosa (Wesmael, 1844)blancoburgensis Schmiedeknecht, 1912 (Lathrolestes), Lectotype; syn. n. of Trematopygodes aprilinus (Giraud, 1872)atropos Schmiedeknecht, 1900 (Lissonota), Lectotypedalmatica Schmiedeknecht, 1907 (Lissonota), Lectotype now a synonym of Lissonota bivittata Gravenhorst, 1829thomsoni Schmiedeknecht, 1900 (Lissonota), Lectotype; syn. n. of Lissonota rusticator (Thunberg, 1822)unicincta Holmgren, 1860 (Lissonota), syn. n. of Lissonota rusticator (Thunberg, 1822)ruficoxis Schmiedeknecht, 1900 (Lissonota sulphurifera var.), Lectotype now a synonym of Lissonota fundator (Thunberg, 1822)holmgreni Schmiedeknecht, 1925 (Mesoleius), Lectotypeunifasciatus Schmiedeknecht, 1905 (Microcryptus), Lectotype now a synonym of Pleolophus vestigialis (Förster, 1850)thomsoni Schmiedeknecht, 1913 (Phobetus), Lectotypeautumnalis Schmiedeknecht, 1905 (Phygadeuon), Lectotypehabermehli Schmiedeknecht, 1906 (Pimpla), Lectotype now a synonym of Scambus nigricans (Thomson, 1877)zonatella Schmiedeknecht, 1914 (Pimpla), Lectotype now a synonym of Scambus calobatus (Gravenhorst, 1829)rubrotinctus Schmiedeknecht, 1914 (Scopesus), Lectotypecoxalis Schmiedeknecht, 1905 (Stylocryptus), Lectotype now a synonym of Endasys testaceipes (Brischke, 1891)ornaticornis (Schmiedeknecht, 1897) (Theroscopus), Lectotype described as Hemiteles ornaticornismodestus Schmiedeknecht, 1912 (Thymaris), Lectotyperarus Horstmann, 1990 (Trematopygodes), spec. n.